Effects of PECVD preparation conditions and microstructures of boron-doped polysilicon films on surface passivation of p-type tunnel oxide passivated contacts. (1st November 2022) - Zeng, Yuheng; Ma, Dian; Liu, Zunke; Liao, Mingdun; Xiao, Mingjing; Xing, Haiyang; Lin, Na; Ding, Zetao; Cheng, Hao; Wang, Yude; Liu, Wei; Yan, Baojie; et al.
Abstract: We investigate the effects of plasma-enhanced chemical vapor deposition (PECVD) preparation conditions and microstructures of the boron-doped polysilicon films on the passivation quality of p-type tunnel oxide passivated contact ( p -TOPCon) integrated with plasma-assisted N2 O oxidation (PANO) SiOx . The B2 H6 gas flow, activation temperature, substrate temperature, H2 dilution ratio, and carbon (C)-doped polycrystalline silicon insertion layer are investigated. The best passivation based on plane-surface n-type CZ-Si lifetime sample manifests an implied open-circuit voltage ( iV oc ) of 706 mV, a single-sided saturation current density ( J 0, s ) of 17.9 fA/cm 2, and an effective lifetime ( τ eff ) of 2.25 ms at 1 × 10 15  cm −3, showing a slight improvement compared with the controlled sample featuring an iV oc of 703 mV. Although this passivation quality is one of the best specifications of the p -TOPCon featuring PANO SiOx so far, it is insufficient for industry application. Detailed experimental studies and a numerical simulation suggest that the passivation quality is probably weakened by the boron-induced defects located at the interfacial and beneath the SiOx, whose harmful influence is difficult to offset by the field-passivating effect. Generally, we provide new insight into the bottleneck of the p -TOPCon's passivation and then discuss the new strategies for improving the p -TOPCon's passivation in this paper.